FINANCIAL INCLUSION AND GROWTH OF SMALL AND MEDIUM ENTERPRISES A CASE STUDY OF MAKINDYE URBAN DIVISION, KAMPALA UGANDA A CROSS-SECTIONAL STUDY. - AINEMBABAZI VIOLAH; Abas Rutaro (Student's Journal of Health Research, 2023)
Background This study was based on three objectives which included; financial accessibility and growth of small scale, financial technology and growth of small and medium enterprises, financial literacy and growth of small and medium enterprises. The study was guided by three theories which include; the resource-based theory, neoclassic theory, and finance growth theory.  Methodology The study employed a descriptive study design and sectional survey was used and a sample size of 186 respondents was used from a target population of 360 SMEs operating in the Makindye urban division. Data was collected using questionnaires and analyzed using descriptive statistics (mean and standard deviation) and inferential (correlation and regression) with the aid of SPSS.  Results The study findings concerning the main objective indicated that financial inclusion influences the growth of small and medium enterprises in Makindye urban division, Kampala, Uganda. The findings indicate financial accessibility as a major challenge limiting the growth of SMEs in Makindye urban division since most of the respondents disagreed that they easily access finance financial technology was also another challenge that limited their growth while financial literacy wasn't a challenge to the owners of SMEs in this area. There is a moderate positive significant relationship between financial inclusion and the growth of SMEs in Makindye Urban Division.  Conclusion SMEs around are limited to accessing financial services by financial players financial technology in terms of mobile money and mobile banking are being used in SMEs which is improving their growth. Financial literacy has a positive relationship with the growth of SMEs in Makindye Urban Division Recommendation  There is a need for sensitization of the financial inclusion strategies to the beneficiaries. Financial institutions must make SMEs aware of the importance of full disclosure of the personal and business information required when looking for financial services.